Environmental contamination in Antarctica : a challenge to analytical chemistry - Caroli, Sergio, 1943-; Cescon, Paolo; Walton, D. W. H. (Elsevier, 2001)
This thought-provoking and ambitious volume surveys the causes and extent of environmental contamination in Antarctica, and looks critically at future prospects. It highlights the key role that modern techniques of analytical chemistry play in achieving reliable empirical data in this field and their impact on shaping legal provisions. Written by prominent scientists and experts in Antarctic sciences, this work gives an overview of the studies undertaken by countries to assess the impact of pollution phenomena on the uniquely clean environment of Antarctica. Empirical studies and regulatory issues are evaluated in context with the goal of providing a model approach to more polluted areas of the world.